A Bibliometric Analysis of Nahdlatul Ulama’s Role in Promoting Moderate and Inclusive Islamic Education - Syafii, Hisyam; Husain Azhari; Alaldaya, Rudyn (LAKPESDAM MWCNU Palengaan, 2025)
This study investigates the intellectual contribution of Nahdlatul Ulama to the development of moderate Islamic educational epistemology during the period 1990-2024 using a comprehensive bibliometric approach. The results show a paradigmatic shift from the classical knowledge transmission approach to an inclusive epistemological framework that combines revealed knowledge, rational reasoning, and the wisdom of the masters. Between 2010 and 2015, the concept of neo-ijtihad as a reconstructive methodology emerged. The intellectual structure shows that figures from the National University have built a broad academic collaboration network, strengthening their epistemological position in global discourse. According to the study, NU has succeeded in developing an epistemology of Islamic education that overcomes the dichotomy between tradition and modernity by using contextual hermeneutics. Studi ini menyelidiki kontribusi intelektual Nahdlatul Ulama terhadap perkembangan epistemologi pendidikan Islam moderat selama periode 1990-2024 dengan menggunakan pendekatan bibliometrik komprehensif. Hasilnya menunjukkan pergeseran paradigmatis dari pendekatan transmisi pengetahuan klasik menuju kerangka epistemologi inklusif yang menggabungkan pengetahuan wahyu, penalaran rasional, dan kebijaksanaan. Struktur intelektual menunjukkan bahwa tokoh-tokoh dari Universitas Nasional telah membangun jaringan kerja sama akademik yang luas, yang memperkuat posisi epistemologi mereka dalam diskursus global. NU berhasil mengembangkan epistemologi pendidikan Islam yang mengatasi dikotomi antara tradisi dan modernitas dengan menggunakan hermeneutika kontekstual. Ini menawarkan opsi untuk mengatasi polarisasi dalam pendidikan agama dan memberikan kontribusi signifikan untuk pengembangan pendidikan Islam inklusif di era modern.